2021
DOI: 10.2174/2211536609666200722125737
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling of Epithelial Ovarian Cancer Identifies New Markers of Tumor Subtype

Abstract: Background: Epithelial ovarian cancer (EOC) is often challenging to diagnose, even though histological examination. microRNA (miRNA or miRNA) is bound to the target messenger RNA (mRNA) and causing the mRNA molecules are silenced. The identification of miRNA expression-based EOC subtypes is considered a critical means of prognostication. So far, the studies on EOC subtypes have not been well characterized. Objective: This study aimed to confirm the existence of miRNAs in EOC and to assess their potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…24 MiR-127-3p was found to be a significantly underexpressed miRNA in epithelial OC, so it could be used as a biomarker for epithelial OC. 25 Bi et al suggested that overexpressed miR-127-3p targeted BAG5 to restrain epithelial OC proliferation and invasion. 26 Also, Xia et al indicated that miR-127 played an anti-cancer role in OC.…”
Section: Discussionmentioning
confidence: 99%
“…24 MiR-127-3p was found to be a significantly underexpressed miRNA in epithelial OC, so it could be used as a biomarker for epithelial OC. 25 Bi et al suggested that overexpressed miR-127-3p targeted BAG5 to restrain epithelial OC proliferation and invasion. 26 Also, Xia et al indicated that miR-127 played an anti-cancer role in OC.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the regulation of miRNA genes, a group of six chromosomes, 19 miRNAs clustered on chromosome 19, and seven clusters were up-regulated on chromosome 14, DNMT-inhibitor decitabine inhibitor, showing that miRNAs can be controlled by DNA methylation [26]. What's more, an overall, collective tumor-MiRNAs' suppressive effect has been suggested by Drosha and Dicer down-regulation, involving two enzymes in the processing of miRNA, being significantly connected with an early stage of ovarian cancer and poor prognosis [27,28].…”
Section: Microrna Dysregulation In Ovarian Cancermentioning
confidence: 99%
“…The dysregulation of particular miRNAs can differ between subtypes of OC. For instance, the overexpression of miR-483 occurs in serous epithelial ovarian cancer (EOC), but does not occur in non-serous EOC [ 102 ]. As demonstrated in voluminous publications, miRNA dysregulation affects a variety of cellular processes that contribute to oncogenesis in a wide variety of cancers.…”
Section: Mirna Dysregulation In Cancermentioning
confidence: 99%